2016
DOI: 10.1371/journal.pone.0148762
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Two Melanoma-Associated Antigens Suggest Allosteric Regulation of Effector Binding

Abstract: The MAGE (melanoma associated antigen) protein family are tumour-associated proteins normally present only in reproductive tissues such as germ cells of the testis. The human genome encodes over 60 MAGE genes of which one class (containing MAGE-A3 and MAGE-A4) are exclusively expressed in tumours, making them an attractive target for the development of targeted and immunotherapeutic cancer treatments. Some MAGE proteins are thought to play an active role in driving cancer, modulating the activity of E3 ubiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…Structural studies have revealed that the MHD consists of two tandem winged-helix (WH) motifs, referred to as WH-A and -B (Figures 3C, D) [26, 27]. Each WH features a characteristic helix-turn-helix motif packed against a three-stranded antiparallel β-sheet “wing”, however, WH-B also contains additional α-helices [26, 27].…”
Section: Overview Of the Mage Familymentioning
confidence: 99%
See 4 more Smart Citations
“…Structural studies have revealed that the MHD consists of two tandem winged-helix (WH) motifs, referred to as WH-A and -B (Figures 3C, D) [26, 27]. Each WH features a characteristic helix-turn-helix motif packed against a three-stranded antiparallel β-sheet “wing”, however, WH-B also contains additional α-helices [26, 27].…”
Section: Overview Of the Mage Familymentioning
confidence: 99%
“…Each WH features a characteristic helix-turn-helix motif packed against a three-stranded antiparallel β-sheet “wing”, however, WH-B also contains additional α-helices [26, 27]. Overall, the MAGE-A3 and -A4 MHD structures share the same relative orientation and both exhibit a peptide extension binding into the conserved cleft between the two WH motifs; however, the C-terminus of MAGE-A4 is more closely associated with the rest of the molecule and forms a longer section of α-helix [27]. …”
Section: Overview Of the Mage Familymentioning
confidence: 99%
See 3 more Smart Citations